Diagnostic ability of EUS-FNA for pancreatic solid lesions with conventional 22-gauge needle using the slow pull technique: a prospective study. (July 2014) - Kin, Toshifumi; Katanuma, Akio; Yane, Kei; Takahashi, Kuniyuki; Osanai, Manabu; Takaki, Ryo; Matsumoto, Kazuyuki; Gon, Katsushige; Matsumori, Tomoaki; Tomonari, Akiko; Maguchi, Hiroyuki; Shinohara, Toshiya; et al.
Abstract: Objective. Endoscopic ultrasonography-guided fine needle aspiration (EUS-FNA) using the slow pull technique (SP-FNA) has recently attracted attention as an effective tissue acquisition technique. However, efficacy of SP-FNA with a 22-gauge conventional needle remains unclear. The aim of this study is to evaluate the diagnostic ability of SP-FNA with a 22-gauge needle. Material and methods. Patients with a pancreatic solid lesion were prospectively enrolled in this study. SP-FNA was performed at two needle passes with a 22-gauge needle. One dedicated pathologist evaluated the obtained samples in terms of quantity (Grade 0: scant; Grade 1: inadequate; Grade 2: adequate), quality (Grade 0: poor; Grade 1: moderate; Grade 2: good), and blood contamination (Grade 0: significant; Grade 1: moderate; Grade 2: low), and provided a pathological diagnosis. Additional EUS-FNA was performed by applying suction (SA-FNA). The evaluation points were as follows: diagnostic accuracy of SP-FNA compared with that of SA-FNA, and the quantity, quality, and blood contamination level of SP-FNA-obtained samples. Results. We enrolled 40 cases. The diagnostic accuracy of SP-FNA was 90% (36/40). There was no significant difference in the accuracy between SP-FNA and SA-FNA (90% vs. 90%, p = 1.000). The samples obtained using SP-FNA were assessed as Grade 2 for quantity in 29 cases (73%), quality in 31 (78%), and blood contamination in 25 (63%). Conclusions. Adequate, high-quality, and unsubstantially blood-contaminated samples could be obtained using SP-FNA. The diagnostic ability of SP-FNA was 90%, which appeared to be similar to that of SA-FNA.